DEVELOPMENT OF BILAYER TABLETS OF LOSARTAN POTASSIUM AND METFORMIN HYDROCHLORIDE LAYER USING NATURAL GUMS AS POLYMERS: bilayer tablets of losartan and metformin - KADIYAM, RAJYALAKSHMI; R, KAVYA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The aim of this research work was to develop and evaluate a bilayer formulation of losartan potassium and metformin hydrochloride for the treatment of diabetic patients with hypertension. In the present study, losartan potassium as immediate-release (IR) layer and metformin hydrochloride as a sustained-release (SR) layer were selected. Methods: The polymers selected were fenugreek gum, sweet potato starch, and ispaghula gum as natural disintegrants for IR layer and guar gum, xanthan gum, and pectin for SR layer. Bilayer tablets were developed by employing the two layers. Results: For IR layer, L4 formulation with 5% ispaghula gum as natural disintegrant showed 98.94% drug release was selected as an optimized layer. For sustained layer, F2 formulation with 18.75% guar gum as drug retardant showed 97.17% drug release was selected as optimized layer. Optimized formulation followed zero-order kinetics. When the release data was plotted into Higuchi and Korsmeyer-Peppas equations, then it was confirmed that the optimized formulation exhibited a Fickian diffusion type drug release. Conclusion: Tablets prepared with 5% ispaghula gum and 18.75% guar gums as drug retardants were found to be useful for bilayer tablet formulation with desired drug release characteristics.